Atiya's Journeys : A Muslim Woman from Colonial Bombay to Edwardian Britain - Lambert-Hurley, Siobhan; Sharma, Sunil (Karachi Oxford University Press, 2014)
This is the original English translation of the first Indian Muslim woman's experiences in the 'West'. Atiya Fyzee's (1877-1967), travelogue-cum-diary was published in an Urdu journal and then in 1922 as a book Zamana-i-Tahsil. The narrative is unique as it moves away from formulaic European travelogues by Indian men and places particular emphasis on 'everyday' activities of women and subaltern classes, dimensions which appeal to general readers and researchers alike today. Alongside lively accounts of local elites and prominent Indians abroad, Atiya provides descriptions of their clothing, meals, servants, homes, and mannerisms. The lucid translation and 48 photographs-some of them rare, are accompanied by meticulous annotations to the narrative and an introduction that provides the context.
Include Illustrations, Appendices, Bibliography and Index.
A Muslim Woman from Colonial Bombay to Edwardian Britain.
Keywords: Travel -- Fyzee-Rahamin, Atiya Begum, 1876-1967 -- Muslim women -- Travelers' writings, Urdu